2020
DOI: 10.18632/aging.103819
|View full text |Cite
|
Sign up to set email alerts
|

D-galactose induces senescence of glioblastoma cells through YAP-CDK6 pathway

Abstract: Treatment of glioblastoma using radiotherapy and chemotherapy has various outcomes, key among them being cellular senescence. However, the molecular mechanisms of this process remain unclear. In the present study, we tested the ability of D-galactose (D-gal), a reducing sugar, to induce senescence in glioblastoma cells. Following pretreatment with D-gal, glioblastoma cell lines (C6 and U87MG) showed typical characteristics of senescence. These included the reduced cell proliferation, hypertrophic morphology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Several previous studies have revealed that YAP‐CDK6 pathway inhibits cellular senescence (Q. Xie et al., 2013 ; X. Xu et al., 2020 ; Yang et al., 2021 ). Consistent with previous studies, in our studies, several lines of evidences suggest that YAP‐CDK6 signaling mediates D‐gal‐induced senescence of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several previous studies have revealed that YAP‐CDK6 pathway inhibits cellular senescence (Q. Xie et al., 2013 ; X. Xu et al., 2020 ; Yang et al., 2021 ). Consistent with previous studies, in our studies, several lines of evidences suggest that YAP‐CDK6 signaling mediates D‐gal‐induced senescence of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4.9 | SAβ-gal staining SAβ-gal staining kit (G1580, Solarbio) was adopted to assess cellular senescence according to the protocol clearly provided by the manufacturer, as previously described (X. Xu et al, 2020).…”
Section: Induction Of Astrocyte Senescencementioning
confidence: 99%
See 3 more Smart Citations